2017
DOI: 10.1002/hec.3542
|View full text |Cite
|
Sign up to set email alerts
|

Will you still need me, will you still feed me when I'm 64? The health impact of caregiving to one's spouse

Abstract: Informal care may substitute for formal long‐term care that is often publicly funded or subsidized. The costs of informal caregiving are borne by the caregiver and may consist of worse health outcomes and, if the caregiver has not retired, worse labor market outcomes. We estimate the impact of providing informal care to one's partner on the caregiver's health using data from the Survey of Health, Ageing, and Retirement in Europe. We use statistical matching to deal with selection bias and endogeneity. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
4
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 34 publications
5
61
4
3
Order By: Relevance
“…Therefore, it is becoming more common for spouses to take on the caregiving role (Lawn & McMahon, 2014). In Europe, spouses provide about a third of all informal care (de Zwart, Bakx, & van Doorslaer, 2017). A survey done in Singapore reported that the spouses made up the second largest group of informal caregiver after adult children (Chan, Malhotra, Rush, & Østbye, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is becoming more common for spouses to take on the caregiving role (Lawn & McMahon, 2014). In Europe, spouses provide about a third of all informal care (de Zwart, Bakx, & van Doorslaer, 2017). A survey done in Singapore reported that the spouses made up the second largest group of informal caregiver after adult children (Chan, Malhotra, Rush, & Østbye, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To deal with the potential endogeneity between caregiving and own health, we start from the economic intuition behind the caregiving decision as presented by De Zwart et al (2017). According to their model, a set of elements affect the caregiving decision.…”
Section: Methodsmentioning
confidence: 99%
“…Using FE models they controlled for time constant heterogeneity, however they did not consider selection into caregiving based on time-variant elements such as previous health. The studies making use of matching (Brenna and Di Novi, 2016;de Zwart et al, 2017;Schmitz and Westphal, 2015), addressed endogeneity of caregiving by statistically matching caregivers and non-caregivers on observable characteristics. By matching on pre-treatment variables, these papers make it credible that treatment is random conditional on controls and hence that an average treatment effect on the treated can be identified.…”
Section: Earlier Work On Health Effects Of Informal Caregivingmentioning
confidence: 99%
“…Studien zeigen auch negative Auswirkungen der Angehörigenpflege auf die physische Gesundheit, die sich bspw. in der Vernachlässigung einer gesunden Lebensweise [13] und erhöhtem Medikamentenkonsum [9,14] zeigen.…”
Section: Introductionunclassified